Behaviour Disorders Related to Drug Abuse Among Secondary School Students in Kenya. - King’endo, Madrine (IISTE, 2015)
The purpose of this study was to find out the behavior disorders displayed by secondary school students as a result of substance abuse. This would assist to train teachers on specialized intervention methods so that they can have knowledge on how to curb drug menace in learning institutions. The students were interrogated about substance abuse practices, use and the factors that lead them to abuse substances. Questionnaires were used to collect data from students and teachers involved in guiding and counseling programs. The findings indicate that students abused drugs and substances and reacted differently, developing different behavior disorders. Their responses revealed that there was no drug abuse program in schools and student addicted to drugs were not attended to. What the teachers revealed indicated that they did not have any training on drug abuse problems and lacked skills and knowledge to deal with drug related behavior disorders among students. Future research and implications for teacher training are discussed.
Keywords: addiction; abuse; behavior problem; special needs students; specialized intervention; dependency; substances